Transcatheter closure of multiple ventricular septal ruptures after acute myocardial infarction: a case report highlighting the role of 3D transthoracic echocardiography - Tengku Winda Ardini; Yuke Sarastri; Joy Wulansari Purba; Yasdika Imam Taufik; Suci Asriri; Ali Nafiah Nasution (The Egyptian Heart Journal)
Abstract Background Post-infarct ventricular septal rupture (PI-VSR) is a rare complication of acute myocardial infarction (AMI) but has very serious implications. Managing PI-VSR using transcatheter closure (TCC) presents varying challenges depending on the patient’s condition. The aim of this study is to present a highly challenging case of multiple VSRs as a complication of AMI. Case presentation: A 59-year-old male was admitted with symptoms of shortness of breath, dyspnea on exertion, orthopnea, and swelling of the lower extremities. He had typical chest pain related to infarction 2 weeks before his admission. On electrocardiogram (ECG) examination, evidence of an old myocardial infarction in the infero-antero-lateral regions was seen. Echocardiography showed mild mitral and tricuspid regularities. The left ventricular (LV) systolic function was mildly compromised, with a global ejection fraction of 44%. There was also a left-to-right VSR shunt in the apical region of the LV. Multiple defects as outlined by 3D transthoracic echocardiography (TTE)—the largest measuring 17 mm. Given the high risks of open-heart surgery, a percutaneous closure of the VSR was carried out using a 21 mm atrial septal defect (ASD) occluder. The device was satisfactorily placed, and there was an improvement in the clinical condition of the patient. He was discharged after his 8-day stay in the hospital. Conclusion Our study emphasizes that echocardiography with 3D imaging provides a more detailed view of the size and shape of the rupture and serves as a valuable modality for guiding the percutaneous transcatheter VSR closure procedure.